Physical Appearance of Commercial Herbal Eco-Green Soap Bar Combination of Madeira Vine Leaf Extract and Citronella Oil - Karimatulhajj, Hanifah; Rohmansyah, Ryan; Haura; Dzikra; Soibatun (APPLIED SCIENCE AND TECHNOLOGY REASERCH JOURNAL, 2024)
Herbal Eco-green soap is made by saponification using cold or hot process soap that reacts the lye with vegetable oil (soap base) and herbal component. Coconut oil is a vegetable oil that gave a nice hardness and foaming to the soap bar. There are two types of coconut oil on the market, namely coconut oil without a filtration process (unrefined) which contain more fatty acid and that has been filtered (refined) which contains less fatty acid. The free fatty acid from vegetable oil that is not saponified would affect the mushy soap and the rancid smell because of any matter that not saponified. The herbal extract added would affect the soap’s organoleptic and homogeneity. In this study, the organoleptic, homogeneity, and foam stability the as physical appearance of the herbal eco-green soap bar was evaluated for the better choice of coconut oil as a base herbal soap. The soap bar made by cold process and there was divided four group formula. Herbal soap with base soap and herbal component combination of madeira vine leaf extract with citronella oil (F1 and F2) and base soap with coconut oil without herbal component (F3 and F4). Formula 1 and 3 using refined coconut oil and F2 and 4 using non refined coconut oil. The study result that the herbais l soap more mushy and looked green than base soap. Herbal soap with non refined coconut oil more homogeneous (F2) and formula 3 was a hardest soap with white colour. All formulas had moderate foam stability.